PENGARUH EFEKTIVITAS PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN TERHADAP KUALITAS LAPORAN KEUANGAN PADA KANTOR WILAYAH KEMENTRIAN AGAMA KABUPATEN KERINCI: Zesmi Kusmila, Adek Irma Rosi - Kusmila, Zesmi; IrmaRosi, Adek (LPPM STIA Nusantara Sakti, 2023)
This research aims to find out whether the implementation of government accounting standards has an effective effect on the quality of financial reports at the Regional Office of the Ministry of Religion, Kerinci Regency. The data analysis method used is simple linear regression analysis with the help of the SPSS program. The results of research conducted regarding the influence of the effectiveness of implementing government accounting standards on the quality of government financial reports show that Tcount is 33.968 with a significance value of 0.021